Psychometric properties of the Malay-version beck anxiety inventory among adolescent students in Malaysia - Ismail, Nur Husna; Nik Jaafar, Nik Ruzyanei; Woon, Luke Sy-Cherng; Mohd Ali, Manisah; Dahlan, Rahima; Baharuddin, Aimi Nur Athira Putri (Frontiers in Psychiatry, 2023)
Background: The Beck Anxiety Inventory (BAI) is a common tool for screening anxiety symptoms. In Malaysia, the Malay-version 21-item BAI has been previously validated in the Malaysian adult population. However, information regarding its reliability and validity among adolescents below 18 years old is still lacking. The objective of this study is to investigate the psychometric properties of the Malay-version BAI in this population. Methods: The Malay versions of the BAI and the Depression, Anxiety, and Stress Scale (DASS) were administered among a sample of lower secondary school students (n=329, age range: 13-14 years) in Selangor, Malaysia. Cronbach's alpha value for the internal consistency of the Malay-version BAI was determined. The correlation coefficient between the BAI score and DASS anxiety subscale score was calculated to examine convergent validity. The factor structure of the Malay-version BAI was identified by exploratory factor analysis (EFA) using principal axis factoring. Results: The study included 329 respondents, who were predominantly female (58.7%) and Malay (79.9%). The mean Malay-version BAI score was 14.46 (SD=12.39). The Malay-version BAI showed a high level of internal consistency (Cronbach's alpha =0.948) and convergent validity with the DASS anxiety subscale score (r=0.80, p<0.001). The EFA suggested a one-factor solution with the factor loading of all items on the single factor ranging between 0.48 and 0.81. Conclusion: The Malay-version BAI demonstrated good psychometric properties. It can be a valid and reliable screening instrument for anxiety among Malaysian adolescents.